PENGARUH KOMPETENSI SOSIAL DAN KEPRIBADIAN GURU TERHADAP SIKAP MODERAT SISWA DI MI AL HUDA GEMPOLSARI - Siti Rimayatul Alawiyah; Ahmad Ma’ruf; Askhabul Kirom (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2023)
Teachers are considered as planners, as well as moderators of ongoing teaching and learning process activities, teachers are also responsible for motivating their students so they can carry out their learning tasks well. The aim of this research is to determine the influence of Social Competence (X1) and Teacher Personality (X2) on Students' Moderate Attitudes (Y). The research method used in this research is quantitative research. This research uses a causal associative method. The type of instrument used in this research is a non-test instrument with a closed questionnaire. Meanwhile, the data analysis technique in this research uses multiple linear regression. There is a significant influence of the variables Social Competence (X1) and Teacher Personality (X2) simultaneously on Students' Moderate Attitudes (Y1) at MI AL Huda Gempolsari Tanggulangin Sidoarjo. The influence of the Teacher's Social Competence (X1) and Personality (X2) simultaneously on the Student's Moderate Attitude (Y) based on the f test results obtained calculated F value > F table (9.857> 3.32) with significance smaller than 0.05 (0.001 < 0.05)